2016
DOI: 10.3389/fpls.2016.01907
|View full text |Cite
|
Sign up to set email alerts
|

Rubber Trees Demonstrate a Clear Retranslocation Under Seasonal Drought and Cold Stresses

Abstract: Having been introduced to the northern edge of Asian tropics, the rubber tree (Hevea brasiliensis) has become deciduous in this climate with seasonal drought and cold stresses. To determine its internal nutrient strategy during leaf senescence and deciduous periods, we investigated mature leaf and senescent leaf nutrients, water-soluble soil nutrients and characteristics of soil microbiota in nine different ages of monoculture rubber plantations. Rubber trees demonstrate complicated retranslocation of N, P, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 58 publications
(69 reference statements)
1
13
0
1
Order By: Relevance
“…It is probable that even short storage at the site would mean that the leaves were mostly shed: Nutrient-rich leaves may have been left onsite, and a leafless biomass was harvested. Additionally, a considerable amount of nutrients in the senescent leaves were re-translocated [34], and nutrients in the litterfall were recycled [31].…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that even short storage at the site would mean that the leaves were mostly shed: Nutrient-rich leaves may have been left onsite, and a leafless biomass was harvested. Additionally, a considerable amount of nutrients in the senescent leaves were re-translocated [34], and nutrients in the litterfall were recycled [31].…”
Section: Discussionmentioning
confidence: 99%
“…Flowering occurs after leaf fall or during leaf emergence (Delabarre and Serier 1995). During refoliation, mobilization of N and C compounds stored in ligneous tree components sustain bud break and the early leaflet growth (Li et al 2016). Root growth during this period parallels shoot growth, i.e., is rhythmic (Thaler and Pagès 1996a).…”
Section: Phenology and Associated Qualitative Changes In Growth Dynamicsmentioning
confidence: 99%
“…3) (Zhang et al 2015). For instance, it has been shown that 40, 57, and 53% of the N, P, and K stocks in leaves were resorbed by storage tissues at leaf shedding in 5-year-old rubber trees (Li et al 2016). Resorption rates were higher in 13-year-old rubber trees (57)(58)(59)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)and 27% for N,P,K,and Mg,respectively) (Murbach et al 2003;Pollinière and Van Brandt 1964).…”
Section: Phenology and Associated Qualitative Changes In Growth Dynamicsmentioning
confidence: 99%
“…Plants remobilize carbon components and nutrients through internal resources cycling from senescing tissues to maximize the resource use efficiency and to minimize the costs [5]. Thus, remobilization is an internal conservation process which can contribute a substantial annual nutrient supply to increase the resource use efficiency [6]. Owing to the importance of resource resorption for plants, differences in patterns of resource remobilization have been exhaustively studied at the intra-and interspecific levels [3,7,8].…”
Section: Introductionmentioning
confidence: 99%